Proceedings of the International Conference on Educational Psychology and Pedagogy - "Diversity in Education" (ICEPP 2019) 2020
DOI: 10.2991/assehr.k.200130.097
|View full text |Cite
|
Sign up to set email alerts
|

Emotion Regulation in Adolescents

Abstract: The emotional life of adolescents is different from children and adults, they react more strongly to situations that emit emotions, experience negative emotions, feel various mixed emotions, and flare up more quickly in certain situations. This article provides an overview of research on regulation of emotions in adolescents in the past decade. In this article three important points are discussed: 1) factors that contribute to the development of emotional regulation skills in the adolescent phase, 2) the motiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
1
0
2
Order By: Relevance
“…They also found that family members and friends provide adolescents with higher levels of emotional support than teachers for instance. And because adolescents are experiencing storm, discoveries, and are more sensitive to emotions than any other age group (Mulyati et al, 2019;Saimons and Robert (2017), providing them with emotional support is crucial for their social readjustment, especially when they face challenges such as distress, disappointment, and anti-social behaviour. Taking a gender approach to livelihood challenges, Stark et al (2018) argue that family support is a crucial cushion of adolescent girls faced with violence and abuse, as alternative sources of income and livelihood opportunities become scarce.…”
Section: Empirical Review Family Support and Social Reintegration Of ...mentioning
confidence: 99%
“…They also found that family members and friends provide adolescents with higher levels of emotional support than teachers for instance. And because adolescents are experiencing storm, discoveries, and are more sensitive to emotions than any other age group (Mulyati et al, 2019;Saimons and Robert (2017), providing them with emotional support is crucial for their social readjustment, especially when they face challenges such as distress, disappointment, and anti-social behaviour. Taking a gender approach to livelihood challenges, Stark et al (2018) argue that family support is a crucial cushion of adolescent girls faced with violence and abuse, as alternative sources of income and livelihood opportunities become scarce.…”
Section: Empirical Review Family Support and Social Reintegration Of ...mentioning
confidence: 99%
“…Dibandingkan dengan masa dewasa dan anak-anak, remaja mengalami intensitas emosi positif dan negatif yang lebih tinggi, intensitas emosional yang lebih besar, dan instabilitas emosi yang lebih intens (Bailen et al, 2019;Mulyati et al, 2020). Hilt et al (2011) juga menyatakan bahwa remaja memiliki emosi yang lebih labil dibandingkan anak-anak dan dewasa.…”
Section: Diskusiunclassified
“…Timbulnya emosi negatif pada remaja ditandai dengan menangis cemas apabila hasil atau pencapaian yang diinginkan tidak sesuai harapan (Nuroniah et al, 2022). Kehidupan emosional remaja berbeda dengan kehidupan emosional masa anak-anak dan dewasa, remaja bereaksi lebih kuat terhadap situasi yang mengeluarkan emosi (Mulyati et al, 2020) Perubahan fisik menimbulkan dampak psikologis yang tidak diinginkan. Mayoritas remaja lebih banyak memperhatikan penampilan ketimbang aspek lain dalam diri mereka, dan banyak di antara mereka yang tidak suka melihat apa yang terlihat di cermin (Denich & Ifdil, 2015b).…”
Section: Pendahuluanunclassified